Language, Culture and Tourism. Reflections on Europeanization and Identity in Post-socialist Countries, Anita Sujoldžić, ur., Institut za antropologiju – Hrvatsko antropološko društvo, Zagreb, 2013., 187 str - Kelemen, Petra (Array, 2014)
Prikaz zbornika radova: Language, Culture and Tourism. Reflections on Europeanization and Identity in Post-socialist Countries, Anita Sujoldžić, ur., Institut za antropologiju – Hrvatsko antropološko društvo, Zagreb, 2013., 187 str.